Effect of Mn2+ substitution into the hst lattice of ZnO via sol-gel route for boosting the dye-sensitized solar cells performance - Kumbhar, Deepak; Delekar, Sagar; Kumbhar, Sarita; Dhodamani, Ananta; Harale, Namdev; Nalawade, Rekha; Nalawade, Avinash (Chemical Papers, 2021)
In this study, Mn2+ ion is doped in ZnO lattice framework at 1, 3 and 5 wt % by a simple and low-cost sol-gel route to attain improved optoelectronic response. The structural investigation by XRD and Raman analysis explores the formation of hexagonal wurtzite framework with variations in lattice parameters comprising peak intensities favors the Mn doping. The extent of doping was supported by EDS analysis, while XPS confirms doping in + 2 chemical state. The optical investigation by UV-visible and PL provides prominent peaks that also specify peak shifting in order of doping level, while the significant hexagon-shaped nanoparticle (NP) formation was deduced in SEM and TEM micrographs. These proficient ZnO NPs have been deposited on fluorine-doped tin oxide (FTO) conducting glass plate by doctor-blade technique to get photoanodes. The electrical performance of these photoanodes especially photocurrent generation was investigated under standard AM 1.5 one sun illuminations. The highest photoconversion efficiency was attained for 3% Mn-doped ZnO photoanode after xanthene-based organic dye sensitization with output efficiency (eta%) of 0.25% higher than 0.03% of bare ZnO. The comparable ionic radii with exactly half-filled 3d orbital simply overlap with the ZnO valence bond responsible for enhanced overall structural and optical properties that beneficial for DSSCs performance.
Keywords: gel; Mixed dye; Mn-doped ZnO; Photoelectrochemical cell; Sol&#8211

Effect of Mn2+ substitution into the hst lattice of ZnO via sol-gel route for boosting the dye-sensitized solar cells performance (Apr, 10.1007/s11696-021-01615-w, 2021) - Kumbhar, Deepak; Delekar, Sagar; Kumbhar, Sarita; Dhodamani, Ananta; Harale, Namdev; Nalawade, Rekha; Nalawade, Avinash (Chemical Papers, 2021)